Improving Children’s Moral Values Through Al-Barokah Madrasah in Kota Daro 1 Village, Rantau Panjang District, Ogan Ilir Regency - Tamsik Udin; Afif Alfiyanto; Aprianti Hastuti; Muhamad Yahya; Ahmad Fadil Mediwinata (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to provide an understanding of children's moral values ??or attitudes and moral attachment to religion. The object of this research is the children of Madrasah Al-Barakah. This research was conducted at the Nurul Islam Mosque from 10.00 to finished on Monday, Wednesday, and Saturday in Kotadaro 1 Village, Rantau Panjang District, Organ Ilir Regency, South Sumatra Province. The research method used was a qualitative descriptive method. The data collection technique used in this study is the method of observation and documentation, which means going directly to the location to observe the behavior and activities of individuals at the research site. The results of this study indicate that in the teaching and learning process, it is necessary to apply the learning method to tell stories while learning or playing because children can understand them carefully. So children can practice what they have learned in their studies. In daily life, for example, in the field of morality, children have better morals.